Avaliação do efeito de parâmetros de processos nas características microestruturais do cimento Portland - Silva, Vilmar Manoel da (2021)
The production of Portland cement by increasing milling additions is an important sustainability challenge aimed at reducing the CO2 emissions impacts from the chain of cement production. The mineralogical and polymorphic characteristics of the C3S on the clinker contribute to its reactivity and the implementation of the additions on the cement composition. Thus, this study aimed to evaluate the effects of the industrial process parameters on the morphology and dimensions of alite crystals and characterize their influence on the cement reactivity and mechanical strength. The experimente analyzed industrial clinker by optical microscopy, XRF and DXR tests for micro structural and mineralogical characterization. The results showed the isolate and interacted effects from the process variables on the C3S generation in relation to their dimension and polymorphous. As a result, there were obtained models defined by the main identified variables that can be used to quantitatively estimate the polymorphsand dimensions of the alite crystals generated in the production process. It was also verified that cements with predominance of M1 show higher mechanical strengths.